Comparison of Universal Mental Health Screening to Students Already Receiving Intervention in a Multitiered System of Support. (May 2018) - Splett, Joni W.; Trainor, Kathryn M.; Raborn, Anthony; Halliday-Boykins, Colleen A.; Garzona, Marlene E.; Dongo, Melissa D.; Weist, Mark D.
Despite schools increasingly adopting multitiered systems of support (MTSS) for prevention and intervention of mental health concerns, many are slow to adopt universal mental health screening (UMHS), a core MTSS feature, due to concerns about their limited capacity to meet the needs of all identified. In this study, we examined differences in the number and characteristics of students who would be identified for intervention services when UMHS in an MTSS were added to those students already receiving social, emotional, and behavioral supports. In a sample of 3, 744 students in Grades 1 to 5 from six schools, 679 (18.1%) additional students were identified by screening, representing a 180.1% increase in students identified with behavioral risk or need for mental health interventions. Using a series of stepwise logistic regression analyses, we identified significant predictors of newly identified students including gender, number of office discipline referrals, and externalizing, internalizing, and adaptive behavior ratings. Findings are discussed in relation to opportunities for prevention and the systems needed in an MTSS to meet the needs of newly identified students.